Pre and post conception risk factors in PROM - Choudhary, Manisha; Rathore, Samta Bali; Chowdhary, Jai; Garg, Swati (International Journal of Research in Medical Sciences, 2017)
Background: The objective of the study was to evaluate the pre conception and post conception risk factors in cases of premature rupture of membranes (PROM). Methods: Two hundred pregnant women that were hospitalized at Mahatma Gandhi Medical College and Hospital from 1st January 2013 to 31st December 2013 with PROM (>28 Weeks) were evaluated for various risk factors of PROM. Results: Low socio-economic status, cervical manipulation, urogenital infections, malpresentation, coitus, hydraminos, multifetal gestation and smoking significantly increase the risk of PROM. Conclusions: Pre and post conception identification of various factors causing PROM can prevent premature deliveries and it’s complications to some extent.